PENANGANAN PERILAKU AGRESIVITAS ANAK USIA DINI DI TAMAN KANAK-KANAK ISLAM TERPADU HARVISYAH - Syahruddin Damanik (STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to determine the form of services provided to deal with aggressive behavior in early childhood along with the supporting and inhibiting factors for handling aggressive behavior in early childhood in the Harvisyah Integrated Islamic Kindergarten. The research method used is qualitative with a case study approach. Where the data collection techniques carried out by researchers are through observation, interviews and documentation as well as data analysis techniques used through data triangulation for data reduction, data presentation and presentation of conclusions. The results showed that the form of service provided by: 1) early detection, 2) acceptance, 3) PAIKEM, 4) reward, 5) exemplary, 6) comfortable environment, 7) empathy development, 8) punishment. While the supporting factors that influence the handling of aggressive behavior in early childhood are the school's concern for the problems faced by teachers and good cooperation between stakeholders. While the inhibiting factors are early problems at home affecting children's behavior at school, handling that is not in harmony between school and home, and limited time for handling aggressive behavior at school.